33.6k views
5 votes
What algebraic expression must be subtracted from y2+5y-1 and 3y2-2y+4 to give you the sum of 2y2+7y-2

User Gegenwind
by
6.0k points

1 Answer

4 votes

Answer:
2y^2-4y+5

Explanation:

The complete exercise is: "What algebraic expression must be subtracted from the sum of
y^2 + 5y - 1 and
3y^2-2y + 4 to give
2y^2 + 7y-2 as the result?"

For this exercise it is necessary to remember that a sum is the result of an addition. Then, if you need to find the sum of
y^2 + 5y - 1 and
3y^2-2y + 4 , you need to add them by combining the like terms.

You also need to remember the multiplication of signs:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-\\(+)(-)=-

So, you get that the sum of those expression is the following:


(y^2 + 5y - 1)+(3y^2-2y + 4)=y^2 + 5y - 1+3y^2-2y + 4=4y^2+3y+3

Since you must find the algebraic expression asked in the exercise, you need to subtract the expression
2y^2 + 7y-2 from that sum calculated above.

Therefore, you get:


(4y^2+3y+3)-(2y^2 + 7y-2)=4y^2+3y+3-2y^2- 7y+2=2y^2-4y+5

Then, the algebraic expression asked is:


2y^2-4y+5

User Intcreator
by
5.7k points